2021
DOI: 10.1371/journal.pcbi.1008576
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale simulations of biological cell sorting driven by differential adhesion follow diffusion-limited domain coalescence regime

Abstract: Cell sorting, whereby a heterogeneous cell mixture segregates and forms distinct homogeneous tissues, is one of the main collective cell behaviors at work during development. Although differences in interfacial energies are recognized to be a possible driving source for cell sorting, no clear consensus has emerged on the kinetic law of cell sorting driven by differential adhesion. Using a modified Cellular Potts Model algorithm that allows for efficient simulations while preserving the connectivity of cells, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…At very high value of p 0 ( p 0 > 30), the individual cells can actually start to break apart (see S13(G) and S13(K) Fig for p 0 = 36), which is an artifact of the Potts model [ 52 ]. We note that this does not appear to directly affect our results in the range of parameters that we have considered, as we do not see any significant change in mean cluster size ( ) as we increase p 0 for p 0 > 30 compared to at p 0 = 30.…”
Section: Resultsmentioning
confidence: 99%
“…At very high value of p 0 ( p 0 > 30), the individual cells can actually start to break apart (see S13(G) and S13(K) Fig for p 0 = 36), which is an artifact of the Potts model [ 52 ]. We note that this does not appear to directly affect our results in the range of parameters that we have considered, as we do not see any significant change in mean cluster size ( ) as we increase p 0 for p 0 > 30 compared to at p 0 = 30.…”
Section: Resultsmentioning
confidence: 99%
“…One of the earliest attempts of simulating cell segregation is the Cellular-Potts-Model (CPM) of Glazier and Graner [ 12 , 13 ], in which segregation results from differential adhesion. While the observed segregation indices display a logarithmic decay, successive studies concluded that the segregation indices actually follow a logarithmic decay only initially and settle to an algebraic one for longer times [ 16 18 , 32 , 34 , 35 ]. Nakajima and Ishihara [ 17 ] used the CPM to study the effects of even and uneven cell type ratios on the segregation process.…”
Section: Introductionmentioning
confidence: 99%
“…He measured the segregation indices over time, which showed a maximal algebraic decay with exponent of 1/4. Durand [ 32 ] used a CPM with modified update algorithm, which allows for simulation of larger number of cells over longer times while preserving cell connectivity. He observed an asymptotic algebraic decay with an exponent of 1/4 and concluded that the previously reported scaling with exponent 1/3 is only transitory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At very high value of p 0 (p 0 > 30), the individual cells can actually start to break apart (see S13(G) and S13(K) Fig for p 0 = 36), which is an artifact of the Potts model [52]. We note that this does not appear to directly affect our results in the range of parameters that we have considered, as we do not see any significant change in mean cluster size (N ) as we increase p 0 for p 0 > 30 compared to at p 0 = 30.…”
Section: Plos Computational Biologymentioning
confidence: 99%